PENGARUH LATIHAN BATUK EFEKTIF DALAM MENGATASI GANGGUAN BERSIHAN JALAN NAFAS PADA PASIEN PNEUMONIA DI RUANG IGD RS TK II PELAMONIA MAKASSAR - Umrah Shari Darwis; Ernasari; Andi Yuliana; Rochfika (Jurnal Kesehatan, 2025)
Pneumonia is a lower respiratory tract infection with high morbidity and mortality rates, especially in the elderly. A common nursing problem is impaired airway clearance due to the inability to cough effectively, resulting in accumulation of secretions and worsening shortness of breath. This condition requires appropriate nursing interventions to help optimize the patient's respiratory function. One intervention that can be provided is effective coughing exercises. These exercises aim to help expel secretions, increase pulmonary ventilation, and improve oxygenation. The method used in this scientific paper is a case study with a nursing process approach that includes assessment, diagnosis, intervention, implementation, and evaluation. The focus of the intervention is effective coughing exercises for pneumonia patients in the Emergency Room of Pelamonia Class II Hospital, Makassar.Evaluation results showed improvements after effective coughing exercises, marked by increased coughing ability, reduced sputum volume and viscosity, and decreased shortness of breath. The application of effective coughing techniques significantly improved airway clearance in clients with pneumonia, thereby reducing their respiratory rate to within the normal range.